Odpowiedzi

2010-04-06T22:37:41+02:00
A) -3x = 2x-10 /-2x
-5x = -10 /÷(-5)
x = 2

b) 2x-2 = 7-x /+x
3x-2 = 7 /+2
3x = 9 /÷3
x = 3

c) 10 = 4-2x /-4
6 = -2x /÷(-2)
x = -3

d) -(2x-1) = 4 /×(-1)
2x-1 = -4 /+1
2x = -3 /÷2
x = -2/3

e) 2(x+1) = x
2x+2 = x /-x
x+2 = 0 /-2
x = -2

f) 2t-(3t+1) = 6
2t-3t-1 = 6 /+1
-t = 7 /×(-1)
t = -7

g) -(4+x) = 2(3-x)
-4-x = 6-2x /+2x
-4+x = 6 /+4
x = 10

h) 3(y+6)-y = 2(y+9)
3y+18-y = 2y+18 /-2y
18 = 18
równanie tożsamościowe

i) (x-7)-2(3x+5) = 3
x-7-6x-10 = 3
-5x-17 = 3 /+17
-5x = 20 /÷(-5)
x = -4
2010-04-06T22:38:03+02:00
A) -5x=-10
5x=10
x=2
b)3x=9
x=3
c)2x=-6
x=-3
d)-2x+1=4
-2x=3
x=-1,5
e)2x+2=x
x=-2
f)2t-3t+1=6
-t=5
t=-5
g)-4-x=6-2x
x=10
h)3y+18-y=2y+18
2y+18=2y+18
0=0
i)x-7-6x-10=3
-5x-17=3
-5x=20
x=-4

Mam nadzieję że pomogłam. Pozdrawiam cieplutko :*